The The Effectiveness of Virtual Ice Breaker Strategy to Improve Students’ Speaking Skill in Online Learning - Ulfa Ainul Hayat; Slamet Riyadi; Prayogo Hadi Sulistio (LEAD (Language, Education and Development), 2024)
This research is aimed at investigating the effectiveness of Virtual Ice Breaker strategy in improving students’ speaking skill in online learning. A quasi experimental design was employed with two classes of the seventh graders at SMP Negeri 2 Purwokerto selected with cluster random sampling as sampling method. The students were divided into two groups namely the experimental group and the control group. The data were obtained through speaking test, observation and interview. The speaking assessment was covering pronunciation, grammar, vocabulary, fluency and comprehension. The computation results showed that Virtual Ice-Breaker strategy was effective in improving the students’ speaking skill where the experimental group got the best score (80.14) than the control group (73.13). Furthermore, in determining the final result, the Independent Sample T-Test was calculated. The significance score (Sig. 2-tailed) was 0.000 < 0.05, it means the Alternative Hypothesis was accepted and Null Hypothesis was rejected where there was a significant effect between the experimental and the control group. In other words, students’ speaking skill have improved. This result was supported with the observation and interview in experimental group. The students gave a good response and showed enthusiasm during the use of the Virtual Ice-Breaker strategy in speaking skill. In conclusion, the use of Virtual Ice-Breaker strategy in teaching speaking is effective to improve students’ speaking skill in online learning of the seventh grade students in SMP N 2 Purwokerto. The teachers may try to take advantage of Ice-Breaker stragey to be utilized in their online classroom activities to conduct an effective and interesting learning atmosphere.